Optimalisasi Desentralisasi Fiskal: Upaya Peningkatan Kesejahteraan Daerah Tertinggal di Indonesia - Auliya Harisa Salsabela; Darmawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Abstract and Keywords must be written in English, in italic style, and containa brief description of the research background, objectives, methods, findings, andimplications. The abstract is written in one paragraph with a single space (maximum200 words), without any reference or formula